Prevalence and prognosis of respiratory muscle weakness in heart failure patients with preserved ejection fraction. (January 2020) - Hamazaki, Nobuaki; Kamiya, Kentaro; Matsuzawa, Ryota; Nozaki, Kohei; Ichikawa, Takafumi; Tanaka, Shinya; Nakamura, Takeshi; Yamashita, Masashi; Maekawa, Emi; Noda, Chiharu; Yamaoka-Tojo, Minako; Matsunaga, Atsuhiko; et al.
Abstract: Background: Although respiratory muscle weakness (RMW) is known to predict prognosis in patients with heart failure with reduced ejection fraction (HFrEF), RMW prevalence and its prognosis in those with preserved ejection fraction (HFpEF) remain unknown. We aimed to investigate whether the RMW predicted mortality in HFpEF patients. Methods: We conducted a single-centre observational study with consecutive 1023 heart failure patients (445 in HFrEF and 578 in HFpEF). Maximal inspiratory pressure (PImax ) was measured to assess respiratory muscle strength at hospital discharge, and RMW was defined as PImax <70% of predicted value. Endpoint was all-cause mortality after hospital discharge, and we examined the influence of RMW on the endpoint. Results: Over a median follow-up of 1.8 years, 134 patients (13.1%) died; of these 53 (11.9%) were in HFrEF and 81 (14.0%) in HFpEF. RMW was evident in 190 (42.7%) HFrEF and 226 (39.1%) HFpEF patients and was independently associated with all-cause mortality in both HFrEF (adjusted hazard ratio [HR]: 2.13, 95% confidence interval [CI]: 1.17–3.88) and HFpEF (adjusted HR: 2.85, 95% CI: 1.74–4.67) patients. Adding RMW to the multivariate logistic regression model significantly increased area under the receiver-operating characteristic curve (AUC) for all-cause mortality in HFpEF (AUC including RMW: 0.78, not including RMW: 0.74, P = 0.026) but not in HFrEF (AUC including RMW: 0.84, not including RMW: 0.82, P = 0.132). Conclusions: RMW was observed in 39% of HFpEF patients, which was independently associated with poor prognosis. The additive effect of RMW on prognosis was detected only in HFpEF but not in HFrEF. Graphical abstract: Image 1 Highlights: Respiratory muscle weakness (RMW) was observed in 39% of patients with HFpEF. RMW was associated with poor prognosis in both patients with HFrEF and HFpEF. RMW showed the additive effect for risk prediction only in patients with HFpEF. Respiratory muscle assessment is useful for risk prediction in HFpEF patients.